The Salient Motives for Malaysia Aviation Industry Sustainability: An Explorative Study on Business, Management and Technology Components in Aviation Management Program in Malaysia - Nor Aida Abdul Rahman; Mohammad Fakhrulnizam Mohammad; Nor Hisham Ghafar; Mohamed Idrus Abdul Moin; Azlina Ali (International Journal of Supply Chain Management, 2020)
The purpose of this research is to develop a comprehensive evaluation framework of three important elements, namely business, management, and technology embedded in the newly developed Master of Science program in aviation management. A Focus group interview has been adopted in this study with the involvement of aviation management faculty members and also panel members from the Board of Studies (BOS). Two prominent aviation practitioners and two leading academicians with aviation background were called for a focus group discussion and the meeting held for six (6) hours. Alignments of the course offered need to be formed to link with the aviation industry 4.0 and aviation industry 5.0. This study reveals the critical needs and issues at the industry perspective and drives new areas for an academician to focus on the syllabus and research. This study bridges the gap between industry and academicians by keeping scholars and practitioners abreast of the timeliest industry-academician framework. It elevated the current thinking necessary for better performance of the industry, as well as the quality of the new proposed master program. This study clearly shows both academic and industry players related needs to establish a new program by consolidating both theoretical development and industry career. Recommendation to all academicians, practitioners, and policymaker are also highlighted in this study.